2001
DOI: 10.1053/joca.2000.0368
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of active TGF-beta-1 in the murine knee joint: evidence for synovial-layer-dependent chondro-osteophyte formation

Abstract: This study shows that overexpression of active TGF-beta1 in the knee joint results in OA-like changes and suggests the synovial lining cells contribute to the chondro-osteophyte formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
181
3
4

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 279 publications
(198 citation statements)
references
References 35 publications
7
181
3
4
Order By: Relevance
“…Active TGF␤ plays a key role in osteophyte formation (40). Furthermore, active TGF␤, injected into mouse knees or continuously overexpressed, leads to joint degeneration (41,42). Osteophyte formation was a prominent feature of OA seen in association with ascorbate in this study.…”
Section: Discussionmentioning
confidence: 50%
“…Active TGF␤ plays a key role in osteophyte formation (40). Furthermore, active TGF␤, injected into mouse knees or continuously overexpressed, leads to joint degeneration (41,42). Osteophyte formation was a prominent feature of OA seen in association with ascorbate in this study.…”
Section: Discussionmentioning
confidence: 50%
“…Given that many of the cDNAs considered to be candidates for this application such as TGF-b1 are pleiotropic, the movement of vector or genetically modified cells into the joint space could cause deleterious side effects within the joint such as fibrosis and ectopic bone formation. 31,32 It should be noted, however, that the CG matrix used in these experiments was not optimized for this method. It is likely that there are methods to incorporate vectors or genetic material more effectively into this scaffold that may provide improved containment and uniformity of gene transfer.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that osteophytes result from the abnormal healing response of subchondral trabeculae, or from the blood vessels penetration into the degrading cartilage [66]. It has been also shown that in OA the patient's osteophytes express TGF-β, which induces osteophyte formation in an experimental model [67,68]. Thomas et al [11] suggested that the action of leptin on bone tissue may be a result of bone marrow stromal cell stimulation and enhanced cell differentiation into osteoblasts with limited differentiation into adipocytes.…”
Section: Adipocytokines In Osteophyte Formationmentioning
confidence: 99%